2015
DOI: 10.1027/1864-9335/a000231
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Deliberative Versus Implemental Mindsets in Time Prediction and Task Accomplishment

Abstract: The Model of Action Phases ( Gollwitzer, 1990 , 2012 ) distinguishes an implemental mindset evoked by planning goal-directed actions, from a deliberative mindset evoked by pondering pros/cons of adopting a particular goal. The present research demonstrates that mindsets affect time predictions. In Study 1 (N = 151), participants in an implemental mindset made shorter time predictions with respect to completing personal goals than participants in a deliberative mindset. In Study 2 (N = 78), we tested a mediatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 48 publications
4
27
0
Order By: Relevance
“…Accordingly, it was impressive that under restricted autonomy decision makers in the present study benefitted from the implemental mindset, presumably since they experienced a boost of achievement motivation in these situations and a deeper processing of available information. Research by Brandstätter et al () fits quite well in this line of argument. These researchers investigated the effects of different mindsets on how early participants acted on a personal goal (returning a report).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Accordingly, it was impressive that under restricted autonomy decision makers in the present study benefitted from the implemental mindset, presumably since they experienced a boost of achievement motivation in these situations and a deeper processing of available information. Research by Brandstätter et al () fits quite well in this line of argument. These researchers investigated the effects of different mindsets on how early participants acted on a personal goal (returning a report).…”
Section: Discussionsupporting
confidence: 61%
“…There were several explanations for our findings. Previous research that investigated decision processes through eye‐tracking (Rahn et al, ) found indicators of increased achievement motivation after the induction of the implemental mindset (see also Brandstätter et al, ). Individuals in an implemental state of mind showed a higher number of fixations of all goal‐relevant information in lottery‐choice tasks (probabilities and lottery outcomes) than participants in the deliberative mindset, especially when decisions were rather difficult (Rahn et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was aligned with our hypothesis of slower decisions in the deliberative mindset due to more extensive information search in this state of mind. It is also consistent with prior evidence of slower goal accomplishment in the deliberative mindset (relative to the implemental mindset; V. Brandstätter et al, ). It should be noted, though, that the task in the study by V. Brandstätter et al (; return a report to the experimenter) was to be accomplished within a much longer period of time, that is, within 2 weeks.…”
Section: Discussionsupporting
confidence: 88%
“…It is also consistent with prior evidence of slower goal accomplishment in the deliberative mindset (relative to the implemental mindset; V. Brandstätter et al, ). It should be noted, though, that the task in the study by V. Brandstätter et al (; return a report to the experimenter) was to be accomplished within a much longer period of time, that is, within 2 weeks. Thus, these findings should be linked to our relatively fast economic decisions only with caution.…”
Section: Discussionsupporting
confidence: 88%